PENILAIAN PORTOFOLIO BASED ON COVID-19 CASE DALAM PERKULIAHAN ASESMEN PEMBELAJARAN MATEMATIKA SEBAGAI INOVASI ASESMEN BERMAKNA DI ERA NEW NORMAL - Eka Sulistyawati (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
Portfolio is a comprehensive assessment that is used to monitor students progress and assess student learning outcomes. Portfolio assessment based on covid-19 case is a portfolio assessment technique that gives students opportunity to apply mathematical material, namely inter-rater reliability to analyze cases related to the effects of covid-19. This research is a qualitative descriptive study with 59 students of IAIN Kediri as research subjects. To monitor students progress and assess student learning outcomes, analytic assessment rubric and self assessment rubric are used. The results showed that there were 11 categories of covid-19 cases analyzed, namely the number of covid-19 cases, users of land and air transportation, awareness of behavior during New Normal, government and economic assistance, regional vulnerability status, family welfare, users of online meeting applications, visitors to public facilities, sales of communication devices, users of shopping online sites, and sports during the pandemic. In addition, the results showed that 86.67% of the total students were able to use nominal and ordinal categories in calculation process.